Convenient synthesis of 5-methylene-4-substituted-2(5H)-furanones - Mahajan, Vishal A.; Shinde, Popat D.; Borate, Hanumant B.; Wakharkar, Radhika D. (Tetrahedron Letters, 2005)
A synthesis of novel 4-(substituted)benzyl-5-methylene-2(5H)-furanones involving Stobbe condensation of substituted aldehydes with ethyl levulinate followed by treatment with acetic anhydride in the presence of sodium acetate, has been developed. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: 5-methylene-2(5H)-furanones; acetic anhydride; arylaldehydes; ethyl levulinate; sodium acetate

Microwave promoted solvent-free one-pot synthesis of N,N `-disubstituted urea derivatives - Jadhav, Vinod H.; Deshpande, S. S.; Borate, Hanumant B.; Wakharkar, R. D. (Journal of Chemical Research-S, 2005)
An efficient one-pot synthesis of N,N -disubstituted urea derivatives from substituted anilines, ethyl chloroformate and methyl anthranilate or methyl 3-amino-2-butenoate under microwave irradiation is reported.
Keywords: Anilines; methyl 3-amino-2-butenoate; methyl anthranilate; Microwave; urea derivatives

Synthesis of substituted tetrahydro-1H-xanthen-1-ones and xanthenes - Patil, M. L.; Borate, Hanumant B. (Journal of Chemical Research, 2005)
A short and an efficient methodology for the synthesis of substituted tetrahydro-1H-1-xanthenones and xanthenes is described.
Keywords: balanol; diarylmethanes; tetrahydro-1H-xanthen-1-ones; Xanthenes

Efficient N-arylation of amines catalyzed by Cu-Fe-hydrotalcite - Jadhav, Vinod H.; Dumbre, Deepa K.; Phapale, Vilas B.; Borate, Hanumant B.; Wakharkar, Radhika D. (Catalysis Communications, 2007)
An efficient N-arylation of amines with aryl halides in presence of heterogeneous recyclable Cu-Fe-hydrotalcite catalyst has been developed. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: amines; Aryl halides; Cu-Fe-hydrotalcite; heterogeneous catalyst; N-arylation

Enantiomeric separation of novel anticancer agent 5-hydroxy-3-(4-methoxyphenyl)-2-(3,4,5-trimethoxyphenyl)-cyclopent-2-en- 1-one - Shinde, Popat D.; Jadhav, Vinod H.; Borate, Hanumant B.; Bhide, Sunil R.; Sonawane, Kiran B.; Wakharkar, Radhika D. (Journal of Chromatography A, 2007)
The enantiomers of 5-hydroxy-3-(4-methoxyphenyl)-2-(3,4,5-trimethoxyphenyl)-cyclopent-2-en- 1-one, a novel anticancer agent, were separated by derivatisation with caronaldehyde, separation of the resulting diastereoisomers of the corresponding esters by silica gel column chromatography and regeneration of alcohols (S)-5-hydroxy-3-(4-methoxyphenyl)-2-(3,4,5-trimethoxyphenyl)-cyclopent-2 -en-1-one and (R)5-hydroxy-3-(4-methoxyphenyl)-2-(3,4,5-trimethoxyphenyl)-cyclopent-2- en- 1-one under aqueous conditions. The absolute configuration of the enantiomers was determined by H-1 NMR studies of the corresponding Mosher esters. Alternatively, the enantiomers were separated by preparative HPLC to collect the (S)- and (R)-5-hydroxy-3-(4-methoxyphenyl)-2-(3,4,5-trimethoxyphenyl)-cyclopent-2 -en-1-ones with high purity which was comparable with that obtained by the chemical method. The details of these methods have been presented herein. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Anticancer; column chromatography; diaryl cyclopentenone; diastereoisomers; enantioseparation; HPLC; Resolution

One-step preparation of alpha-chlorostyrenes - Borate, Hanumant B.; Galkwad, Abaji G.; Maujan, Suleman R.; Sawargave, Sangmeshwer P.; Kalal, Kamalakar M. (Tetrahedron Letters, 2007)
alpha-Chlorostyrenes were prepared via a one-step method involving Friedel-Crafts reaction of various aromatic substrates with acid chlorides in the presence of a heterogeneous Si-Fe catalyst. (c) 2007 Elsevier Ltd. All rights reserved.

Oxidation of benzylic alcohols and sulfides over LaCoO3 and TBHP - Patil, Mahesh L.; Maujan, Suleman R.; Borate, Hanumant B.; Uphade, Balu S. (Arkivoc, 2007)
A simple and efficient methodology has been described for the selective oxidation of secondary benzylic alcohols to the corresponding ketones. In contrast, primary benzylic alcohols afforded dimethyl acetals.
Keywords: acetals; benzylic alcohols; Oxidation; perovskite LaCoO3

Simple and efficient synthesis of thysanone methyl ether - Bulbule, Vivek J.; Koranne, Priti S.; Deshpande, Vishnu H.; Borate, Hanumant B. (Tetrahedron, 2007)
The synthesis of thysanone methyl ether is achieved by employing semivioxanthin methyl ether, which in turn is prepared by the tandem Michael addition of an anion of orsellinate to a substituted dihydropyrone. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: human pathogen; Michael addition; orsellinate derivative; semivioxanthin

Synthesis and evaluation of 4/5-hydroxy-2,3-diaryl(substituted)-cyclopent-2-en-1-ones as cis-restricted analogues of combretastatin A-4 as novel anticancer agents - Gurjar, Mukund K.; Wakharkar, Radhika D.; Singh, Anu T.; Jaggi, Manu; Borate, Hanumant B.; Shinde, Popat D.; Verma, Ritu; Rajendran, Praveen; Dutt, Sarjana; Singh, Gurvinder; Sanna, Vinod K.; Singh, Manoj K.; et al. (Journal of Medicinal Chemistry, 2007)
A new series of 2,3-diaryl-4/5-hydroxy-cyclopent-2-en-1-one analogues replacing the cis double bond of combretastatin A-4 (CA-4) by 4/5-hydroxy cyclopentenone moieties was designed and synthesized. The analogues displayed potent cytotoxic activity (IC50 < 1 mu g/mL) against a panel of human cancer cell lines and endothelial cells. The most potent analogues 11 and 42 belonging to the 5-hydroxy cyclopentenone class were further evaluated for their mechanism of action. Both of the analogues led to cell cycle arrest at G2/M phase and induced apoptosis in endothelial cells. Antitubulin property of 42 was superior to 11 and comparable to CA-4. The compound 42 had better aqueous solubility, metabolic stability, and pharmacokinetic profile than CA-4 and also demonstrated significant tumor regression in the human colon xenograft model. Our data suggests that cis-restricted analogues of CA-4 are a new class of molecules that have the potential to be developed as novel agents for the treatment of cancer.

Transesterification of alpha-haloesters and beta-ketoesters over Mg-Al-hydrotalcites (HT)-like anionic clays - Bulbule, Vivek J.; Borate, Hanumant B.; Munot, Yogesh S.; Deshpande, Vishnu H.; Sawargave, Sangmeshwer P.; Gaikwad, Abaji G. (Journal of Molecular Catalysis A-Chemical, 2007)
Transesterification of alpha-haloesters was achieved by reaction of alcohols in the presence of Mg-Al-HT-like anionic clays. beta-Ketoesters were also transesterified under similar conditions on reaction with alcohols with a wide variety of functional groups. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: alpha-haloesters; beta-ketoesters; heterogeneous catalyst; Hydrotalcites; transesterification

Synthesis of substituted styrenes and stilbenes mediated by palladium on zirconia - Borate, Hanumant B.; Dumbre, Deepa K.; Wakharkar, Radhika D.; Choudhary, Vasant R. (Journal of Chemical Research-S, 2008)
Palladium on zirconia has been found to be an effective catalyst for the synthesis of various substituted styrenes and stilbenes, including biologically active natural products, by reaction of aryl halides with olefins.
Keywords: heterogeneous catalyst; palladium on zirconia; stilbenes; styrenes

Short synthesis of 3,6-disubstituted N-2-thienyl/aryl-indoles - Borate, Hanumant B.; Sawargave, Sangmeshwer P.; Maujan, Suleman R. (Tetrahedron Letters, 2009)
A short synthetic strategy for 3,6-disubstituted-N-2-thienyl/aryl-indoles, involving reaction of substituted 2,4-difluoro/dichloro-styrene epoxide with substituted 2-formylaminothiophenes or substitued N-formylanilins in the presence of a base followed by treatment with an acid, has been developed The method was applied for the synthesis of a number of indoles with a variety of substitutents at 1, 3, and 6 positions of the indole moiety. (C) 2009 Elsevier Ltd All rights reserved.
Keywords: Formylaminothiophene; Gewald synthesis; Indole; Styrene epoxide

Fluconazole analogues containing 2H-1,4-benzothiazin-3(4H)-one or 2H-1,4-benzoxazin-3(4H)-one moieties, a novel class of anti-Candida agents - Borate, Hanumant B.; Maujan, Suleman R.; Sawargave, Sangmeshwer P.; Chandavarkar, Mohan A.; Vaiude, Sharangi R.; Joshi, Vinay A.; Wakharkar, Radhika D.; Iyer, Ramki; Kelkar, Ramesh G.; Chavan, Subhash P.; Kunte, Sunita S. (Bioorganic & Medicinal Chemistry Letters, 2010)
As a part of our program to develop new antifungal agents, a series of fluconazole analogues was designed and synthesized wherein one of the triazole moieties in fluconazole was replaced with 2H-1,4-benzothiazin-3(4H)-one or 2H-1,4-benzoxazin-3(4H)-one moiety. The new chemical entities thus synthesized were screened against various fungi and it was observed that the compounds 4a and 4i are potent inhibitors of Candida strains. The structure-activity relationship for these compounds is discussed. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: antifungal; Benzothiazinone; Benzoxazinone; Fluconazole

Novel hybrids of fluconazole and furanones: design, synthesis and antifungal activity - Borate, Hanumant B.; Sawargave, Sangmeshwer P.; Chavan, Subhash P.; Chandavarkar, Mohan A.; Iyer, Ramki; Tawte, Amit; Rao, Deepali; Deore, Jaydeep V.; Kudale, Ananada S.; Mahajan, Pankaj S.; Kangire, Gopinath S. (Bioorganic & Medicinal Chemistry Letters, 2011)
During our efforts to develop new antifungal agents, a number of hybrid molecules containing furanones and fluconazole pharmacophores were designed and synthesized. The new chemical entities thus synthesized were tested for their potential as antifungal agents against various fungal strains and it was observed that the compounds with general structure 7 were potent inhibitors of Candida albicans ATCC 24433, Candida glabrata ATCC 90030, Candida tropicalis ATCC 750 and Candida neoformans ATCC 34664 while the fluconazole analogues 12 exhibited antifungal activity against Candida albicans ATCC 24433 and Candida glabrata ATCC 90030. The structure-activity relationship for these compounds is discussed. The synthetic strategies used in the present work have potential to prepare a large number of compounds for further refinement of structures to obtain molecules suitable for development as antifungal drugs. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Antifungal activity; Fluconazole; Furanones

One-step synthesis of 4-alkyl-3-aryl-2,6-dicyanoanilines and their use in the synthesis of highly functionalized 2,3,5,6,7-and 2,3,4,5,7-substituted indoles - Sawargave, Sangmeshwer P.; Kudale, Ananada S.; Deore, Jaydeep V.; Bhosale, Dattatry S.; Divse, Jaisingh M.; Chavan, Subhash P.; Borate, Hanumant B. (Tetrahedron Letters, 2011)
A three-component, one-step method for the synthesis of 4-alkyl-3-aryl-2,6-dicyanoanilines involving reaction of alkyl aldehyde, malononitrile and aryl aldehyde in presence of morpholine is reported. Highly functionalized 2,3,5,6,7- and 2,3,4,5,7-substituted indoles were prepared from these dicyanoanilines by reaction with ethyl bromoacetate. These substituted dicyanoanilines and indoles have a potential to be converted into various other compounds taking advantage of various functional groups present in these molecules. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: aldehydes; Dicyanoanilines; indoles; Malononitrile

Solvent-free one-pot synthesis of sulfonephthaleins from saccharin and phenols - Tillu, V. H.; Dumbre, Deepa K.; Borate, Hanumant B.; Wakharkar, R. D.; Choudhary, Vasant R. (Synthetic Communications, 2012)
Sulfonephthaleins can be synthesized in a single pot from saccharin and phenol via the in situ formation of 2-sulfobenzoic anhydride, followed by its reaction with phenol using H2SO4 as the condensing agent, in the absence of any solvent. This solvent-free synthesis is more economical and environmentally benign.
Keywords: H2SO4; Phenols; saccharin; sulfonephthalein

Synthesis of substituted 2,6-dicyanoanilines and related compounds. a review - Borate, Hanumant B.; Kudale, Ananada S.; Agalave, Sandip G. (Organic Preparations and Procedures International, 2012)

One-step method for the synthesis of aryl olefins from aryl aldehydes and aliphatic aldehydes - Borate, Hanumant B.; Gaikwad, Supriya H.; Kudale, Ananada S.; Chavan, Subhash P.; Pharande, Shrikant G.; Wagh, Vitthal D.; Sawant, Vikram S. (Tetrahedron Letters, 2013)
A conceptually new one-step reaction affording unexpected aryl olefinic product from aromatic aldehyde, aliphatic aldehyde and malononitrile in the presence of acetic acid-ammonium acetate under mild reaction conditions without using any metal catalyst is reported. This novel reaction was used to prepare a number of substituted aryl olefins including new molecules. (c) 2013 Elsevier Ltd. All rights reserved.
Keywords: Aliphatic aldehyde; Aromatic aldehyde; Aryl olefin; Dicyanoaniline; Malononitrile

Unusual, selective, reductive, deoxygenation of cyclopentenone alcohols - Bavikar, Suhas R.; Lasonkar, Trupti P.; Chavan, Subhash P.; Borate, Hanumant B. (Tetrahedron Letters, 2014)
A selective, reductive, deoxygenation of 2-aryl-4-hydroxycyclopent-2-en-1-ones to afford 2-aryl-cyclopent-2-en-1-ones was achieved by NaBH4-CeCl3 in methanol. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Cyclopentenone alcohol; Enone; Luche reduction; Reductive deoxygenation

Synthesis and evaluation of thieno[2,3-d]pyrimidin-4(3H)-ones as potential antitubercular agents - Borate, Hanumant B.; Annadate, Ritesh A.; Vagh, Sandip S.; Pisal, Mahesh M.; Deokate, Sagar B.; Arkile, Manisha A.; Jadhav, Nandadeep J.; Nawale, Laxman U.; Sarkar, Dhiman (MedChemComm, 2015)
A number of thieno[2,3-d]pyrimidin-4(3H)-ones were designed, synthesized and screened against Mycobacteria as a part of our program to develop new antitubercular agents. It was observed that some of the compounds have significant antimycobacterial activity against Mycobacterium tuberculosis H37Ra (ATCC 25177) and Mycobacterium bovis BCG (ATCC 35743). The active compounds were studied for cytotoxicity against four cell lines and were found to be non-cytotoxic. The results showed that compounds 13b and 29e were found to exhibit very good antimycobacterial activity (MIC in the range of 6-8 mu M) and the thienopyrimidinones as a class have potential to be developed as antitubercular agents.

Synthesis and evaluation of thieno[2,3-d]pyrimidin-4(3H)-ones as potential antitubercular agents (vol 6, pg 2209, 2015) - Borate, Hanumant B.; Annadate, Ritesh A.; Vagh, Sandip S.; Pisal, Mahesh M.; Deokate, Sagar B.; Arkile, Manisha A.; Jadhav, Nandadeep J.; Nawale, Laxman U.; Sarkar, Dhiman (Medchemcomm, 2016)

Hybrids of thienopyrimidinones and thiouracils as anti-tubercular agents: SAR and docking studies - Pisal, Mahesh M.; Nawale, Laxman U.; Patil, Manoj; Bhansali, Sujit G.; Gajbhiye, Jayant M.; Sarkar, Dhiman; Chavan, Subhash P.; Borate, Hanumant B. (European Journal of Medicinal Chemistry, 2017)
A number of hybrid molecules containing thienopyrimidinones and thiouracil moieties were designed, synthesized and tested against Mycobacterium tuberculosis H37Ra wherein it was observed that the compounds 11-1514 exhibited antitubercular activity in vitro (MIC 7.6–19.1 μg/ml, 12–35 μM) against dormant stage while compound 15 exhibited antitubercular activity in vitro against dormant (MIC 23.4 μg/ml, 41 μM) as well as active (MIC 25.4 μg/ml, 45 μM) stage. Structural modifications of compound 15 were carried out to study the structure-activity relationship and it was observed that compound 18 exhibited antitubercular activity comparable to compound 15. Cytotoxicity studies revealed that these molecules were non-toxic. The docking study of compound 15 showed that there was binding with the active site of mycobacterial pantothenate synthetase. Further docking studies led to the synthesis of the compounds 16 and 17 and the antitubercular activity screening results showed that these compounds have significant antitubercular activity. The compounds 15-18 (MIC 11–29 μg/ml, 19–51 μM) can be used as starting points for further optimization. The synthetic strategies used in the present work have potential to prepare a large number of compounds for further refinement of structures and the present results will be very useful in the development of a new class of antimycobacterial agents.

Synthesis and cell imaging applications of fluorescent mono/di/tri-heterocycl- yl-2,6-dicyanoanilines - Pisal, Mahesh M.; Annadate, Ritesh A.; Athalye, Meghana C.; Kumar, Dipak; Chavan, Subhash P.; Sarkar, Dhiman; Borate, Hanumant B. (Bioorganic & Medicinal Chemistry Letters, 2017)
Synthesis of 3,4,5-triheterocyclyl-2,6-dicyanoanilines, starting from heterocyclic aldehydes and 1,2-diheterocycle-substituted ethanones, is described. 2,6-Dicyanoanilines with one or two heterocyclic substituents have also been synthesized. It was found that some of these molecules have selective cell-staining properties useful for cell imaging applications. The compounds 1g, 10f and 11 were found to stain cytoplasm of the cells in contact but not the nucleus while the compound 12 showed affinity to apoptotic cells resulting in blue fluorescence. The cell imaging results with compound 12 were similar to Annexin V-FITC, a known reagent containing recombinant Annexin V conjugated to green-fluorescent FITC dye, used for detection of apoptotic cells. These compounds were found to be non-cytotoxic and have potential application as cell imaging agents.

Synthesis and cell imaging applications of fluorescent mono/di/tri-heterocyclyl-2,6-dicyanoanilines (vol 27, pg 979, 2017) - Pisal, Mahesh M.; Annadate, Ritesh A.; Athalye, Meghana C.; Kumar, Deepak; Chavan, Subhash P.; Sarkar, Dhiman; Borate, Hanumant B. (Bioorganic & Medicinal Chemistry Letters, 2021)